1994
DOI: 10.1161/01.hyp.23.4.456
|View full text |Cite
|
Sign up to set email alerts
|

High-fructose feeding elicits insulin resistance, hyperinsulinism, and hypertension in normal mongrel dogs.

Abstract: To determine whether chronic high-fructose feeding causes insulin resistance and hypertension in normal dogs, we fed 10 male dogs a normosodic diet containing 60% of the calories as fructose for 20 to 28 days; a control group of 8 dogs was fed a similar diet containing dextrose instead of fructose. In the fructose-fed group, (1) fasting triglyceridemia increased from 35.3±0.63 to 91.9±11.55 mg/dL after 25 days (f <.001); (2) fasting insulinemia increased from 19.0±1.9 to 58.9±7.22 iU/mL after 25 days (P<.001);… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
81
1
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(93 citation statements)
references
References 55 publications
8
81
1
2
Order By: Relevance
“…Among those, Thorburn et al (87) reported an impairment of insulin sensitivity in fructose-fed rats but not in glucose-fed rats when both carbohydrates provided 33 % of total energy. Similar results have been observed in dogs (88,89) and men (90,91) . During a high-sucrose or high-fructose diet in the rat, insulin resistance occurs first in the liver with a decrease in the insulininduced inhibition of glucose liver production (92,93) .…”
Section: Nutrition Research Reviewssupporting
confidence: 89%
See 1 more Smart Citation
“…Among those, Thorburn et al (87) reported an impairment of insulin sensitivity in fructose-fed rats but not in glucose-fed rats when both carbohydrates provided 33 % of total energy. Similar results have been observed in dogs (88,89) and men (90,91) . During a high-sucrose or high-fructose diet in the rat, insulin resistance occurs first in the liver with a decrease in the insulininduced inhibition of glucose liver production (92,93) .…”
Section: Nutrition Research Reviewssupporting
confidence: 89%
“…However, one study performed in dogs and using another method to measure blood pressure confirmed that a highfructose diet increased blood pressure (88) . Finally, in human subjects, an epidemiological study also confirmed that consuming a higher than average amount of fructose increased the risk of developing hypertension (140) .…”
Section: Secondary Diseasesmentioning
confidence: 99%
“…As such, acute ingestion of fructose leads to substantially increased triacylglycerol levels in humans 19,20 and animals. 21,22 In a chronic study in mice, the effects of ad libitum access to drinks containing fructose, sucrose and water on body weight, adiposity and energy metabolism were compared. 23 Not only did the fructosedrinking mice have the greatest increases in body weight, but also in body fat when expressed both in absolute and percentage terms, even though total calorie intake (food and beverages) did not differ between the groups.…”
Section: 17mentioning
confidence: 99%
“…23 Not only did the fructosedrinking mice have the greatest increases in body weight, but also in body fat when expressed both in absolute and percentage terms, even though total calorie intake (food and beverages) did not differ between the groups. 22 In humans,…”
Section: 17mentioning
confidence: 99%
“…Thus, the present study was designed to investigate the effect of dietary raw garlic homogenate on insulin resistance and the associated metabolic syndrome in an established model of type 2 diabetes mellitus characterized by insulin resistance, metabolic syndrome and oxidative stress [12][13][14].…”
Section: Introductionmentioning
confidence: 99%